Pressure-sensitive adhesive matrix with improved adhesion as well as preparation method and application of pressure-sensitive adhesive matrix

By selecting appropriate monomers and functional monomers in the pressure-sensitive adhesive and adopting specific preparation methods, the problem of insufficient adhesion of existing pressure-sensitive adhesives is solved, and the long-lasting adhesion of the patch and efficient drug delivery are achieved.

CN119591775AInactive Publication Date: 2025-03-11SHENYANG PHARMA UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411044191.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing pressure-sensitive adhesive for percutaneous drug delivery is insufficient, which leads to the patch being easily shedded during the treatment process, which cannot meet the drug administration requirements of long-acting drugs, and is also highly lipophilic, poorly compatible with water, and is prone to shedding when the patient takes a bath or sweats on his skin.

Method used

By selecting lipophilic flexible base monomers and hydrophilic hard functional monomers, combined with specific ratios and preparation methods, a pressure-sensitive glue matrix with long-lasting skin adhesion and high-efficiency drug-loading ability was prepared.

Benefits of technology

This enables the patch to maintain skin adhesion after the patient is bathed, improves patch compliance and drug utilization, and reduces the risk of side effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591775A_ABST
    Figure CN119591775A_ABST
Patent Text Reader

Abstract

The invention relates to a transdermal drug delivery patch matrix, in particular to a pressure-sensitive adhesive matrix with improved adhesion as well as a preparation method and application of the pressure-sensitive adhesive matrix. The pressure-sensitive adhesive matrix is prepared from the following raw materials in parts by weight: 40-80 parts of a basic monomer, 5-40 parts of a functional monomer I and 0.1-25 parts of a functional monomer II, wherein the basic monomer is selected from one or more of acrylic acid-2-ethylhexyl acrylate, n-butyl acrylate, ethyl acrylate, 2-dodecyl acrylate and lauryl methacrylate; the functional monomer I is selected from one or more of acrylamide, N-ethyl acrylamide, N-vinyl pyrrolidone and vinyl acetate; the functional monomer II is selected from one or more of hydroxyethyl acrylate, acrylic acid, acrylamide, N-hydroxyethyl acrylamide and hydroxyethyl methylacrylate. The pressure-sensitive adhesive matrix disclosed by the invention has efficient drug loading capacity, lasting skin adhesion and relatively good water compatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a transdermal drug delivery patch matrix, in particular to a pressure-sensitive adhesive matrix with improved adhesion, and a preparation method and application thereof. Background Art

[0002] Since the 1960s, transdermal drug delivery systems have received increasing attention because of their many advantages, such as avoiding the first-pass effect, maintaining a constant drug delivery rate, reducing side effects, and shortening the drug delivery time. Patches are one of the most widely used dosage forms in transdermal drug delivery systems and can be divided into matrix type and reservoir type. Among them, matrix patches have become the most popular patch form due to their simple preparation, good patient compliance, low risk of accidental overdose, and low possibility of abuse. Matrix patches use pressure-sensitive adhesive as the matrix, and their quality is directly determined by the pressure-sensitive adhesive and its excipients, so the selection of pressure-sensitive adhesive is very important.

[0003] At present, pressure-sensitive adhesives for percutaneous drug delivery are mainly produced and listed by countries such as the United States and Germany, including polyacrylates, polyisobutylenes, silicones and hot-melt pressure-sensitive adhesives. Among them, polyacrylate pressure-sensitive adhesives have good biocompatibility, good physical and chemical stability, and good miscibility with most drugs. Therefore, they are the most commonly used pressure-sensitive adhesives in patches, occupying more than half of the market share. However, these products still have some shortcomings, such as poor adhesion, which can cause the patch to accidentally fall off during treatment, and cannot meet the drug delivery requirements of long-acting drugs. Insufficient cohesion can reduce the shear adhesion of the patch, causing the patch to slip during use, cold flow, leaving a black ring on the skin, and reducing the patient's compliance with treatment. In addition, these pressure-sensitive adhesives are highly lipophilic and have poor compatibility with water. They are easy to fall off when the patient takes a bath or the skin sweats. For long-acting patches, patients will avoid taking a bath to prevent the patch from falling off, which further reduces the patient's compliance with treatment. Therefore, it is urgent to develop a pressure-sensitive adhesive with lasting adhesion and water compatibility. Summary of the invention

[0004] The object of the present invention is to provide a pressure-sensitive adhesive matrix.

[0005] Another object of the present invention is to provide a method for preparing the pressure-sensitive adhesive matrix.

[0006] Another object of the present invention is to provide application of the pressure-sensitive adhesive matrix.

[0007] A pressure-sensitive adhesive matrix according to a specific embodiment of the present invention is made of the following raw materials in parts by weight: 40-80 parts of a base monomer, 5-40 parts of a functional monomer I, 0.1-25 parts of a functional monomer II,

[0008] The base monomer is selected from one or more of 2-ethylhexyl acrylate, n-butyl acrylate, ethyl acrylate, 2-dodecyl acrylate and lauryl methacrylate;

[0009] Functional monomer I is selected from one or more of acrylamide, N-ethylacrylamide, N-vinyl pyrrolidone and vinyl acetate;

[0010] The functional monomer II is selected from one or more of hydroxyethyl acrylate, acrylic acid, acrylamide, N-hydroxyethyl acrylamide and hydroxyethyl methacrylate.

[0011] In the present invention, the base monomer selects a lipophilic soft component to provide basic adhesion for the pressure-sensitive adhesive; the functional monomer I and the functional monomer II select a hydrophilic hard part, and through a special ratio, provide cohesion for the pressure-sensitive adhesive, wherein the interaction between the hydroxyl group, the amide carbonyl group or the skin can further improve the adhesion.

[0012] According to a specific embodiment of the present invention, a method for preparing a pressure-sensitive adhesive matrix comprises the following steps:

[0013] (1) putting the base monomer, functional monomer I and functional monomer II into a reaction kettle in sequence, adding a solvent, and mixing the raw materials uniformly;

[0014] (2) controlling the temperature of the reactor to between 70°C and 80°C, and adding an initiator dropwise to the reactor;

[0015] (3) After the reaction process is maintained for 10-12 hours, the mixture is cooled to room temperature and a diluent is added to dilute the mixture to obtain the pressure-sensitive adhesive matrix.

[0016] According to the method for preparing a pressure-sensitive adhesive matrix according to a specific embodiment of the present invention, in step (1), before the raw materials are put into the reactor, the reactor is filled with nitrogen or argon.

[0017] Preferably, the present invention provides a method for preparing the pressure-sensitive adhesive matrix described above, comprising the following steps:

[0018] (1) Weigh the required raw materials according to the formula;

[0019] (2) Fill the reactor with nitrogen or argon.

[0020] (3) Put the base monomer, functional monomer I and functional monomer II into a reaction kettle in sequence, add a solvent, start stirring, and mix the raw materials evenly.

[0021] (4) Dissolve the initiator in a solvent and place it in a constant pressure funnel;

[0022] (5) The temperature of the reactor is controlled between 70-80°C, the constant pressure funnel is opened, and the initiator solution is added dropwise to the reactor. All the solution is added dropwise within 1-5 hours.

[0023] (6) After the reaction process is maintained for 10-12 hours, the mixture is cooled to room temperature, and a diluent is added to reduce the solid content of the pressure-sensitive adhesive matrix, thereby finally obtaining a pressure-sensitive adhesive matrix.

[0024] According to the method for preparing a pressure-sensitive adhesive matrix according to a specific embodiment of the present invention, in step (2), the initiator is selected from one or more of benzoyl peroxide, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), ammonium persulfate and potassium persulfate.

[0025] Preferably, the initiator is 0.001-5 parts, and the solvent for dissolving the initiator is 10-100 parts;

[0026] According to the method for preparing a pressure-sensitive adhesive matrix according to a specific embodiment of the present invention, in step (3), the dilution solvent is selected from one or more of ethyl peroxide, acetone, methanol, ethanol, dichloromethane and chloroform.

[0027] Preferably, the dilution solvent is 50-150 parts by weight.

[0028] The present invention also provides application of the pressure-sensitive adhesive matrix in a transdermal administration preparation.

[0029] A transdermal patch according to a specific embodiment of the present invention comprises the pressure-sensitive adhesive matrix and an active ingredient dispersed in the pressure-sensitive adhesive matrix, wherein the amount of the active ingredient is 2-20 wt %.

[0030] The active ingredient dosage of 2-20 wt % means that the mass of the active ingredient accounts for 2-20% of the total mass of (patch matrix + active ingredient).

[0031] Preferably, the active ingredient is selected from one or more of donepezil, nicotine, loxoprofen, etodolac, propranolol, tulobuterol, clonidine, ibuprofen and ketoconazole.

[0032] The present invention also provides a method for preparing the above transdermal patch, comprising the following steps:

[0033] The active ingredient (drug) is dissolved in an organic solvent, dispersed in the pressure-sensitive adhesive, and coated on the anti-adhesive layer after stirring, dried, and covered with a backing layer.

[0034] Specifically, the drug is fully dissolved in an organic solvent and then dispersed in a pressure-sensitive adhesive, stirred evenly and then transferred and coated on a release layer, dried at 40-75° C. for 10-60 min, then covered with a backing layer, and punched into transdermal patches of a certain size and specification.

[0035] The thickness of the drug-loaded transdermal absorption patch of the present invention is 40-120 μm.

[0036] Beneficial effects of the present invention:

[0037] The pressure-sensitive adhesive matrix of the present invention is a random copolymer with a weight average molecular weight between 400,000-800,000 Da, a polydispersity coefficient between 1.05-1.5, a solid content between 25-55 wt %, and a glass transition temperature of -50°C-10°C.

[0038] The solid content of the matrix is ​​between 25-55wt%, and the glass transition temperature of the matrix is ​​between -50°C and 10°C.

[0039] The pressure-sensitive adhesive prepared by the present invention has long-lasting skin adhesion, solves the problem of insufficient adhesion of the pressure-sensitive adhesive matrix, and the prepared patch can still maintain skin adhesion after the patient bathes. In addition, the pressure-sensitive adhesive prepared by the present invention also has efficient drug loading capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 The water absorption weight gain measurement results of Examples 34-36 are shown.

[0042] Figure 2 The human skin adhesion test results of Examples 34-36 are shown.

[0043] Figure 3 The in vitro skin permeation curves of the drugs in Examples 25, 28 and 31 are shown.

[0044] Figure 4 The in vitro skin permeation curves of the drugs in Examples 37, 38 and 39 are shown.

[0045] Figure 5 The drug release profiles of Examples 25, 28 and 31 are shown.

[0046] Figure 6 The drug release profiles of Examples 26, 29 and 32 are shown.

[0047] Figure 7 The drug release profiles of Examples 27, 30 and 33 are shown. DETAILED DESCRIPTION

[0048] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0049] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0050] The weight parts mentioned in the present invention may be kilograms, grams or milligrams.

[0051] In the present invention, the backing layer used is not particularly limited as long as it can be used for a patch, and preferably a polyethylene composite film, an ethylene / vinyl acetate copolymer film, a polyurethane film, a polyester composite film or a nonwoven fabric is used.

[0052] The anti-adhesive layer used is not particularly limited, and any anti-adhesive layer commonly used in patches can be used. Preferably, the surface is treated with silicone oil to release adhesion or is a fluorine-containing polyester film or a fluorine polymer coated polyester film.

[0053] The present invention provides a pressure-sensitive adhesive matrix, which is prepared from the following raw materials in parts by weight:

[0054] Basic monomer: 2-ethylhexyl acrylate 40-80 parts;

[0055] Functional monomer 1 N-vinyl pyrrolidone 5-40 parts;

[0056] Functional monomer II: N-hydroxyethyl acrylamide 0.1-25 parts;

[0057] Also includes 50-200 parts of solvent I: one or more selected from ethyl acetate, acetone, methanol, ethanol, dichloromethane and chloroform;

[0058] Solvent II 10-50 parts: one or more selected from ethyl acetate, acetone, methanol, ethanol, dichloromethane and chloroform;

[0059] Solvent III 50-150 parts: one or more selected from ethyl acetate, acetone, methanol, ethanol, dichloromethane and chloroform;

[0060] Initiator 0.1-5 parts: one or more selected from benzoyl peroxide, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), ammonium persulfate and potassium persulfate

[0061] The preparation method of the above-mentioned pressure-sensitive adhesive matrix is ​​as follows:

[0062] 66 parts of base monomer 2-ethylhexyl acrylate, 28 parts of functional monomer I N-vinyl pyrrolidone, and functional monomer II were slowly dripped into the reactor within 2 hours through a pressure funnel and reacted for 10 hours. Then 50 parts of solvent III acetic acid and 6 parts of N-hydroxyethyl acrylamide were added to the reactor and mixed. 150 parts of solvent I ethyl acetate were added and the temperature was controlled at 74°C. 0.4 parts of initiator 2,2'-azobisisobutyronitrile and 20 parts of solvent II ethyl acetate were mixed. Ethyl acetate was added and stirred evenly to obtain a durable skin adhesion polyacrylate pressure-sensitive adhesive.

[0063] Example 1

[0064] The reactor was filled with nitrogen. 54 parts of the base monomer 2-ethylhexyl acrylate, 26 parts of the functional monomer I N-ethylacrylamide, and 15 parts of the functional monomer II hydroxyethyl acrylate were added to the reactor and mixed, and 200 parts of the solvent I methanol were added. The temperature was controlled at 73°C, and 0.5 parts of the initiator 2,2'-azobisisobutyronitrile was mixed with 60 parts of the solvent II methanol, loaded into a constant pressure funnel, and slowly dripped into the reactor within 3 hours. The reaction was allowed to react for 12 hours, and then 100 parts of the solvent III methanol were added and stirred evenly to obtain a durable skin-adhesive polyacrylate pressure-sensitive adhesive.

[0065] Example 2

[0066] The reactor was filled with nitrogen. 60 parts of the base monomer ethyl acrylate, 30 parts of the functional monomer I N-vinyl pyrrolidone, and 10 parts of the functional monomer II acrylic acid were added to the reactor and mixed, 150 parts of the solvent I ethyl acetate were added, the temperature was controlled at 80°C, 0.4 parts of the initiator 2,2'-azobis(2,4-dimethylvaleronitrile) was mixed with 50 parts of the solvent II ethyl acetate, loaded into a constant pressure funnel, and slowly dripped into the reactor within 1 hour, reacted for 24 hours, and then 100 parts of the solvent III ethyl acetate were added and stirred evenly to obtain a durable skin-adhesive polyacrylate pressure-sensitive adhesive.

[0067] Example 3

[0068] Fill the reactor with nitrogen. Add 60 parts of the base monomer 2-dodecyl acrylate, 30 parts of the functional monomer IN-vinyl pyrrolidone, and 10 parts of the functional monomer II acrylamide into the reactor and mix, add 150 parts of the solvent I ethyl acetate, control the temperature at 80°C, mix 0.4 parts of the initiator 2,2'-azobis(2,4-dimethylvaleronitrile) with 50 parts of the solvent II ethyl acetate, put into a constant pressure funnel, slowly drip into the reactor within 1 hour, react for 24 hours, then add 100 parts of the solvent III ethyl acetate and stir evenly to obtain a durable skin-adhesive polyacrylate pressure-sensitive adhesive.

[0069] Example 4

[0070] The reactor was filled with nitrogen. 64 parts of the basic monomer n-butyl acrylate, 24 parts of the functional monomer I N-vinyl pyrrolidone, and 12 parts of the functional monomer II hydroxyethyl acrylate were added to the reactor and mixed, 120 parts of the solvent I ethyl acetate were added, the temperature was controlled at 74°C, 0.4 parts of the initiator 2,2'-azobisisobutyronitrile was mixed with 20 parts of the solvent II ethyl acetate, loaded into a constant pressure funnel, slowly dripped into the reactor within 2 hours, reacted for 12 hours, and then 40 parts of the solvent III ethyl acetate were added and stirred evenly to obtain a durable skin-adhesive polyacrylate pressure-sensitive adhesive.

[0071] Example 5

[0072] The reactor was filled with nitrogen. 66 parts of the base monomer 2-ethylhexyl acrylate, 28 parts of the functional monomer I N-vinyl pyrrolidone, and 6 parts of the functional monomer II N-hydroxyethyl acrylamide were added to the reactor and mixed, 150 parts of the solvent I ethyl acetate were added, the temperature was controlled at 74°C, 0.4 parts of the initiator 2,2'-azobisisobutyronitrile was mixed with 20 parts of the solvent II ethyl acetate, loaded into a constant pressure funnel, slowly dripped into the reactor within 2 hours, reacted for 10 hours, and then 50 parts of the solvent III ethyl acetate were added and stirred evenly to obtain a durable skin-adhesive polyacrylate pressure-sensitive adhesive.

[0073] Example 6

[0074] The reactor was filled with nitrogen. 40 parts of the base monomer lauryl methacrylate, 20 parts of the functional monomer I N-vinyl pyrrolidone, and 25 parts of the functional monomer II hydroxyethyl methacrylate were added to the reactor and mixed, 150 parts of the solvent I ethyl acetate were added, the temperature was controlled at 76°C, 0.5 parts of benzoyl peroxide and 20 parts of the solvent II ethyl acetate were mixed, loaded into a constant pressure funnel, slowly dripped into the reactor within 1 hour, reacted for 24 hours, and then 70 parts of the solvent III ethyl acetate were added and stirred evenly to obtain a durable skin-adhesive polyacrylate pressure-sensitive adhesive.

[0075] Application Example Preparation of Patch

[0076] Example 7

[0077] Tulobuterol was dissolved in 0.6 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 2 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0078] Example 8

[0079] Clonidine was dissolved in 0.6 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 2 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50°C for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0080] Example 9

[0081] Loxoprofen was dissolved in 0.6 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 2 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0082] Example 10

[0083] Etodolac was dissolved in 0.6 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 2 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0084] Embodiment 11

[0085] Ibuprofen was dissolved in 0.6 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 2 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0086] Example 12

[0087] Donepezil was dissolved in 0.6 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 2 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0088] Example 13

[0089] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 7.

[0090] Embodiment 14

[0091] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 8.

[0092] Embodiment 15

[0093] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 9.

[0094] Example 16

[0095] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 10.

[0096] Embodiment 17

[0097] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 11.

[0098] Embodiment 18

[0099] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 12.

[0100] Embodiment 19

[0101] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 7.

[0102] Embodiment 20

[0103] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 8.

[0104] Embodiment 21

[0105] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 9.

[0106] Embodiment 22

[0107] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 10.

[0108] Embodiment 23

[0109] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 11.

[0110] Embodiment 24

[0111] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 12.

[0112] Example 25 (Propranolol-Example 5)

[0113] 0.05-0.2 g of propranolol was dissolved in 1.2 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0114] Example 26 (Loxoprofen - Example 5)

[0115] 0.05-0.2 g of loxoprofen was dissolved in 1.2 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0116] Example 27 (Donepezil - Example 5)

[0117] 0.05-0.2 g of donepezil was dissolved in 1.2 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0118] Example 28 (Propranolol-4098)

[0119] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 25.

[0120] Example 29 (Loxoprofen-4098)

[0121] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 26.

[0122] Example 30 (Donepezil-4098)

[0123] Use of pressure sensitive adhesive 87-4098, and the rest are the same as in Example 27.

[0124] Example 31 (Propranolol-2510)

[0125] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 25.

[0126] Example 32 (Loxoprofen-2510)

[0127] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 26.

[0128] Example 33 (Donepezil-2510)

[0129] Use of pressure sensitive adhesive 87-2510, and the rest are the same as in Example 27.

[0130] Example 34 Blank Example

[0131] 1.2 mL of a 1:1 mixture of dichloromethane and ethanol was mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), applied on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0132] Embodiment 35 87-4098 comparison

[0133] 1.2 mL of a 1:1 mixture of dichloromethane and ethanol was mixed with 4 g 87-4098 were mixed evenly, coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50°C for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0134] Embodiment 36 87-2510 comparison

[0135] 1.2 mL of a 1:1 mixture of dichloromethane and ethanol was mixed with 4 g 87-2510 were mixed evenly, coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50°C for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0136] Embodiment 37

[0137] 0.05-0.2 g of tulobuterol was dissolved in 1.2 mL of a 1:1 mixture of dichloromethane and ethanol, mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5), applied on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0138] Example 38 Comparative Example 87-4098

[0139] Dissolve 0.05-0.2 g of tulobuterol in 1.2 mL of a 1:1 mixture of dichloromethane and ethanol and add 4 g 87-4098 were mixed evenly, coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50°C for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0140] Example 39 Comparative Example 87-2510

[0141] Dissolve 0.05-0.2 g of tulobuterol in 1.2 mL of a 1:1 mixture of dichloromethane and ethanol and add 4 g 87-2510 were mixed evenly, coated on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50°C for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0142] Embodiment 40

[0143] 1.2 mL of a 1:1 mixture of dichloromethane and ethanol was mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 1), applied on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0144] Embodiment 41

[0145] 1.2 mL of a 1:1 mixture of dichloromethane and ethanol was mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 2), applied on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0146] Embodiment 42

[0147] 1.2 mL of a 1:1 mixture of dichloromethane and ethanol was mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 3), applied on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0148] Embodiment 43

[0149] 1.2 mL of a 1:1 mixture of dichloromethane and ethanol was mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 4), applied on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0150] Embodiment 44

[0151] 1.2 mL of a 1:1 mixture of dichloromethane and ethanol was mixed evenly with 4 g of a durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 6), applied on the anti-adhesive layer, left at room temperature for 10 min, then dried at 50° C. for 15 min, and covered with a backing material to prepare a patch with an adhesive layer thickness of 70 μm.

[0152] Performance Testing

[0153] The present invention tests the pressure-sensitive adhesive matrix obtained in Examples 1-6, and the test items include relative molecular mass, solid content, glass transition temperature and polydispersity coefficient.

[0154] (1) Determination of molecular weight and polydispersity coefficient

[0155] The molecular weight and polydispersity coefficient of the pressure sensitive adhesive were determined by gel permeation chromatography. The pressure sensitive adhesive was dissolved in tetrahydrofuran and allowed to stand for 24 hours, and then measured by Waters Alliance e2695 and calibrated with polymethyl methacrylate.

[0156] (2) Determination of solid content

[0157] Weigh 1g of pressure-sensitive adhesive liquid, place it in a culture dish, and dry it at 60°C for 12h. Measure the weight m after drying, and the solid content is m*100%.

[0158] (3) Determination of glass transition temperature

[0159] The glass transition temperature of the pressure sensitive adhesive was determined using differential scanning calorimetry, measured by a Mettler-Toledo thermal analyzer. A dried 20-milliliter sample was placed in an aluminum crucible for thermal analysis. The heating process was -80°C to 40°C at a rate of 5°C / min. The midpoint of the phase change was determined as the glass transition temperature.

[0160] The measurement results are shown in Table 1.

[0161] Table 1 Test results of weight average molecular weight, polydispersity coefficient, solid content and glass transition temperature

[0162] Example 1 Example 2 Example 3 Weight average molecular weight (Da) 423,800±8,000 501,200±9,000 486,200±8,500 Polydispersity coefficient 1.10±0.04 1.12±0.05 1.15±0.05 Solid content (%) 32±2 30±2 50±2 Glass transition temperature(℃) -40.0±1.7 -30.0±1.3 -28.8±2.0 Example 4 Example 5 Example 6 Weight average molecular weight (Da) 658,600±8,500 635,360±6,000 715,220±8,700 Polydispersity coefficient 1.40±0.07 1.31±0.02 1.25±0.05 Solid content (%) 40±2 32±2 40±2 Glass transition temperature(℃) -15.5±1.2 -12.2±1.3 -25.5±1.5

[0163] According to the adhesion determination method of Chinese Pharmacopoeia (2020 edition) 0952, the adhesion of the patches of Examples 25-36, 40-44 was measured, and human skin adhesion test and water absorption rate determination were performed on Examples 34-36.

[0164] (1) Initial adhesion test

[0165] The initial adhesion was measured by the rolling ball ramp stop method with a tilt angle of 45°.

[0166] (2) Holding time measurement

[0167] The patch was adhered to the test steel plate, placed vertically, a 1 kg weight was hung along the direction of the patch, and the time from the patch sliding to falling off was recorded.

[0168] (3) Peel strength measurement

[0169] The 180° peel strength test method was used to measure the peel strength of the patch using a tensile testing machine.

[0170] Water absorption determination

[0171] The samples were cut into 4 cm*4 cm size and placed in deionized water to measure the water absorption and weight gain. Figure 1 .

[0172] like Figure 1 As shown, compared with Example 35 and Example 36, Example 34 has better water absorption performance, which indicates that the preferred pressure-sensitive adhesive can absorb moisture seeping from the skin surface and prevent moisture accumulation to affect patch adhesion.

[0173] (5) Determination of human skin adhesion

[0174] The examples were punched into 12 mm patches, which were applied to the forearms of volunteers. The volunteers were bathed on the 3rd and 6th days, and the number of remaining patches was recorded. The results are shown in Figure 2 .

[0175] Table 2 Adhesion performance test results of different prescription patches

[0176]

[0177]

[0178] Conclusion: As shown in Table 2, Example 34 (the pressure-sensitive adhesive prepared by Example 5) has the best comprehensive adhesion performance, so Example 5 is the preferred formulation for the pressure-sensitive adhesive; Figure 1 As shown in Table 1, before and after drug loading, the adhesion of the durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5) is better than that of the commercially available pressure-sensitive adhesive. 87-4098 and 87-2510 was able to maintain adhesion after the volunteers bathed. This shows that the durable skin adhesion polyacrylate pressure-sensitive adhesive has excellent adhesion properties.

[0179] Drug loading capacity test

[0180] Patches containing gradient drug concentrations were prepared according to Examples 7-24, placed at room temperature for 1 month, and the crystallization was observed under a microscope.

[0181] A series of drug concentrations of drug-pressure-sensitive adhesive mixtures are prepared, wherein the maximum drug concentration without crystallization is the drug loading capacity of the pressure-sensitive adhesive. The experimental results of drug loading capacity determination of 24 are shown in Table 2.

[0182] Table 3. Maximum drug loading of different drugs in different pressure-sensitive adhesives

[0183] Example 7 Example 8 Example 9 Drug loading (w / w, ±1%) 23 35 36 Example 10 Embodiment 11 Example 12 Drug loading (w / w, ±1%) 57 28 25 Embodiment 13 Embodiment 14 Embodiment 15 Drug loading (w / w, ±1%) 15 5 16 Example 16 Embodiment 17 Embodiment 18 Drug loading (w / w, ±1%) 30 10 12 Embodiment 19 Embodiment 20 Embodiment 21 Drug loading (w / w, ±1%) 18 6 21 Embodiment 22 Embodiment 23 Embodiment 24 Drug loading (w / w, ±1%) 42 13 11

[0184] Conclusion: As shown in Table 3, compared with commercially available pressure-sensitive adhesives 87-2510 and Compared with 87-4098, the drug loading capacity of the durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5) is higher.

[0185] In vitro skin permeation test

[0186] A horizontal Franz diffusion cell was used, with fresh pig ear skin as the transdermal barrier, pH 7.4 phosphate buffer as the receptor medium, a magnetic stirrer was used continuously during the experiment, the stirring speed was 400-600rpm, the system temperature was 32°C, and the cumulative permeation of the patch was measured for 24h or 72h. The drug transdermal results are shown in Figure 3-4 .

[0187] The results show that the drug permeation rate of the preferred pressure-sensitive adhesive (Examples 25 and 37) is higher than that of the commercially available 87-4098 (Examples 28, 38), slightly lower than commercially available 87-2510 (Examples 31 and 39), indicating that the preferred pressure-sensitive adhesive has good drug transdermal delivery ability.

[0188] In vitro release assay

[0189] A horizontal Franz diffusion cell was used, with a celluloid membrane as the permeation barrier, the receiving medium was a pH 7.4 phosphate buffer (Example), a pH 7.4 phosphate buffer containing PEG200 (20wt%) (Example), a magnetic stirrer was continuously used during the experiment, the stirring speed was 400-600rpm, the system temperature was 32°C, and the cumulative release amount of the patch for 24h was measured. The drug release results are shown in Figure 5-7 .

[0190] The results show that the drug release rate of the preferred pressure-sensitive adhesive (Examples 25 and 26) is higher than that of the commercially available 87-4098 (Examples 28, 29), slightly lower than commercially available 87-2510 (Examples 31 and 32), indicating that the preferred pressure-sensitive adhesive has good drug release ability and can release the drug more completely.

[0191] Thus, the patch prepared with the durable skin-adhesive polyacrylate pressure-sensitive adhesive (Example 5) has a high drug utilization rate and a moderate drug transdermal rate.

[0192] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A pressure-sensitive adhesive matrix, characterized in that: It is made of the following raw materials in parts by weight: 40-80 parts of basic monomer, 5-40 parts of functional monomer I, 0.1-25 parts of functional monomer II, The base monomer is selected from one or more of 2-ethylhexyl acrylate, n-butyl acrylate, ethyl acrylate, 2-dodecyl acrylate and lauryl methacrylate; Functional monomer I is selected from one or more of acrylamide, N-ethylacrylamide, N-vinyl pyrrolidone and vinyl acetate; The functional monomer II is selected from one or more of hydroxyethyl acrylate, acrylic acid, acrylamide, N-hydroxyethyl acrylamide and hydroxyethyl methacrylate.

2. The method for preparing the pressure-sensitive adhesive matrix according to claim 1, characterized in that: The preparation method comprises the following steps: (1) putting the base monomer, functional monomer I and functional monomer II into a reaction kettle in sequence, adding a solvent, and mixing the raw materials uniformly; (2) controlling the temperature of the reactor to between 70°C and 80°C, and adding an initiator dropwise to the reactor; (3) After the reaction process is maintained for 10-12 hours, the mixture is cooled to room temperature and a diluent is added to dilute the mixture to obtain the pressure-sensitive adhesive matrix.

3. The method for preparing a pressure-sensitive adhesive matrix according to claim 2, characterized in that: Step (1) Before the raw materials are put into the reactor, the reactor is filled with nitrogen or argon.

4. The method for preparing a pressure-sensitive adhesive matrix according to claim 2, characterized in that: In step (2), the initiator is selected from one or more of benzoyl peroxide, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), ammonium persulfate and potassium persulfate.

5. The method for preparing a pressure-sensitive adhesive matrix according to claim 2 or 4, characterized in that: In step (3), the dilution solvent is selected from one or more of ethyl peroxide, acetone, methanol, ethanol, dichloromethane and chloroform.

6. Use of the pressure-sensitive adhesive matrix according to claim 1 or the pressure-sensitive adhesive matrix obtained by the preparation method according to any one of claims 2 to 5 in a transdermal drug delivery preparation.

7. A transdermal patch, characterized in that: The transdermal patch comprises the pressure-sensitive adhesive matrix according to claim 1 or the pressure-sensitive adhesive matrix obtained by the preparation method according to any one of claims 2 to 5, and active ingredients dispersed in the pressure-sensitive adhesive matrix.

8. The transdermal patch according to claim 7, characterized in that The active ingredient is selected from one or more of donepezil, nicotine, loxoprofen, etodolac, propranolol, tulobuterol, clonidine, ibuprofen and ketoconazole.

Citation Information

Patent Citations

  • High-temperature-resistant and low-peel-strength acrylate pressure-sensitive adhesive and preparation method thereof

    CN106520032A

  • Acrylate pressure sensitive adhesive emulsion of PET substrate for battery packaging, preparation method and application thereof

    CN107603527A

  • Rotigotine percutaneous absorption patch, and preparation and application thereof

    CN110638792A

  • Pressure-sensitive adhesive dispersing type red medicine patch and preparation method thereof

    CN114748521A

  • IN3438CH2010A